Pertimbangan Hakim Tentang Penggunaan Keterangan Ahli Sebagai Alat Bukti Dalam Tahap Penyidikan Kasus Pembunuhan - Andi Wulan Rahmadania (Peneliti.net, 2023)
Criminal investigations have become an integral part of the judicial process that seeks material truth, justice in criminal cases, especially murders. This article describes the position and impact of forensic medical evidence on judges' reasoning. This research is more of a normative research. However, the status of forensic opinion is based on the dualism of expert evidence. Expert testimony in the form of a statement or Visa et Repertum can still be treated as expert evidence, while evidence in the form of expert testimony also applies to documentary evidence, but completes the duality of evidence. in a decision based on the opinion of a forensic expert. Forensic science plays a role in determining cause-and-effect relationships between an action and the outcome that causes harm, health problems, or death to someone (causative verb). The fields of law and medicine are very closely related to the chain of evidence in murder cases due to the ignorance of investigators and judges in resolving murder cases involving the human body and soul, this research seeks the role of forensics to assist investigators. . Based on the results of field investigations, the role of forensic assistance is very important to clarify the circumstances of the case. Obstacles must be avoided in order for homicide detectives to solve criminal cases and obtain valid evidence, but the role of forensics is not always successful. The investigation revealed that the police should coordinate with the doctors and base the investigation on justice.